Fairness in Financial Contribution - Javad Javan-Noughabi (Journal of Public Health International, 2018)
A health financing perspective examines fairness in financial contribution, considering risk pooling, progressive funding, and protection against catastrophic spending.
Keywords: Fairness In Financial Contribution